2018
DOI: 10.1039/c8ra02512f
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen doped hierarchically structured porous carbon fibers with an ultrahigh specific surface area for removal of organic dyes

Abstract: Recently, tremendous efforts have been devoted to creating inexpensive porous carbon materials with a high specific surface area (SSA) as adsorbents or catalysts for the efficient removal of organic pollutants. Here, activated porous carbon fibers with hierarchical structures were designed and constructed by an electrospinning technique, in situ polymerization, and activation and carbonization processes. Benefiting from the precursor fiber design and subsequent activation techniques, the activated porous carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Also, activated carbon nanofiber membranes can degrade dyes. Electrospun membranes made of PAN, a precursor of activated carbon, had porous hierarchical structure (Zhu et al 2018;Lin et al 2017) after exposing to high thermal treatment. Also, the oxidation power of the carbon materials could be enhanced by the incorporation of cobalt into the spinning solution (Lin et al 2017).…”
Section: Nanofibers For Wastewater Treatmentmentioning
confidence: 99%
“…Also, activated carbon nanofiber membranes can degrade dyes. Electrospun membranes made of PAN, a precursor of activated carbon, had porous hierarchical structure (Zhu et al 2018;Lin et al 2017) after exposing to high thermal treatment. Also, the oxidation power of the carbon materials could be enhanced by the incorporation of cobalt into the spinning solution (Lin et al 2017).…”
Section: Nanofibers For Wastewater Treatmentmentioning
confidence: 99%
“…A maximum surface area of 802 m 2 g −1 was observed for the activated CFs after heating process at 850 °C for 5 h. Nitrogen adsorption–desorption isotherms revealed that the resultant activated CFs were mostly microporous. Carbon fibers derived from PAN/PBZ precursor exhibited a tunable porous structure with ultrahigh specific area of more than 2000 m 2 g −1 and pore volume of 1.12 cm 3 g −1 , providing new insights into the design and development of metal‐free adsorbents, catalysts, or carbon supports …”
Section: Polybenzoxazine/carbon Materials Compositesmentioning
confidence: 99%
“…Supercapacitors assembled with porous carbon as electrodes exhibited large specific capacitances and provided good cycle stability. Liu et al [ 17 ] combined the electrospinning technology, the in situ polymerization and carbonization processes, and the manufacturing process to produce a nitrogen-doped graded porous carbon fiber material, which can remove organic dyes efficiently. It also mentioned that in multi-stage pore materials, macropores can provide efficient mass transfer [ 18 , 19 ], while micropores/mesopores provided a large surface area for the dispersion of HPW [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%